A Study of Selected Representative Organ Pieces by Rachel Laurin - Cheng, S.S. (Université du Kansas, 2015)
Over the course of the last decade the organ works of Canadian composer Rachel Laurin (b. 1961) have gained critical acclaim among professional organists. Her organ music has captured the attention of American and Canadian organists, resulting in a series of commissions for new organ works. To date, there are over thirty-two compositions for organ solo. This document explores stylistic issues in Laurin's compositions for solo organ and for organ with other instruments. Pieces that have been selected for in-depth study include Chromatic Fantasietta, Scherzetto, Toccatarina (to Katarina) and Asian Legend from Twelve Short Pieces, Volume 3, op. 64, Étude Héroïque, Op.38, and the Sonata for Organ and Horn, Op.60, II. On a Painting by Thomson. At the outset of the document an overview of Canadian organ culture is provided, followed by an introduction to Laurin's life and works. Subsequently, a structural and harmonic analysis of Laurin's compositions is presented. As this analysis will reveal, the expressive dimensions of her works embrace elements of Romanticism and Impressionism.

La Bolduc. Parlure et accents de ses chansons - Duguay, Sylvie (Éditions Sylvie Duguay, 2015)

ECM+ Génération 2014 : regards sur les quatre compositeurs lauréats (1re partie) - Henry, Symon (Circuit, 2015)
Publisher: Les Presses de l’Université de Montréal

ECM+ Génération 2014 : regards sur les quatre compositeurs lauréats (2e partie) - Henry, Symon (Circuit, 2015)
Publisher: Les Presses de l’Université de Montréal

Elkahna Talbi : femme de paroles - Lalonde, Catherine (Jeu : revue de théâtre, 2015)
Publisher: Cahiers de théâtre Jeu inc.

Willie Eckstein, Harry Thomas, Vera Guilaroff: Three Montreal Pianists from the Jazz Age - Litchfield, Jack (Autoédition, 2015)

Mountain City Girls: The McGarrigle Family Album - McGarrigle, Anna; McGarrigle, Jane (Random House Canada, 2015)

Dans un grand champ nu. Des récits, des images, des chants - Miville-Deschênes, Monique (Éditions Trois-Pistoles, 2015)

Vie musicale à l'église Saint-Viateur-d'Outremont. Victoria Cartier, première grande figure - Panneton, Hélène (Mémoire vivante, 2015)

From Kitchen To Carnegie Hall: The Story of the Montreal Women's Symphony Orchestra - Rachwal, Maria Noriega (Second Story Press, 2015)
In the 1940s it was unheard of for women to be members of a professional orchestra, let alone play "masculine" instruments like the bass or trombone. Yet despite these formidable challenges, the Montreal Women's Symphony Orchestra (MWSO) became the only all-women orchestra in Canadian history. Formed in 1940, the MWSO became the first orchestra to represent Canada in New York City's Carnegie Hall and one of its members also became the first Canadian black woman to play in a symphony in Carnegie Hall. While the MWSO has paved the way for contemporary female musicians, the stories of these women are largely missing from historical records. From Kitchen to Carnegie Hall illuminates these revolutionary stories, including the life of the incredible Ethel Stark, the co-founder and conductor of the MWSO. Ethel's work opened doors of equal opportunity for marginalized groups and played an important role in breaking gender stereotypes in the Canadian music world.
Keywords: History / Canada / Post-Confederation (1867-); Music / History & Criticism; Music / Individual Composer & Musician